Transformasi Teknologi dalam Sel Surya Film Tipis Generasi Kedua - Susanto Gultom, Noto; Nuri Nilam Sari, Putri; Daniel Saragih, Albert; Shania Anjani, Alena; Dini Farhani, Arini; Anandia Putri, Shakila (Indonesian Society of Applied Science, 2025)
Efficiency and cost are important points in the development of the renewable energy industry, especially solar cells. While the first generation of crystalline silicon-based solar cells had the biggest constraint in cost, the second generation of thin-film solar cells is trying to offer innovations with relatively lower cost but high flexibility compared to the first generation. This article explores the essential developments in the invention of second-generation thin-film solar cells, including materials, performance, and technology. Through their respective fabrication processes, ultra-thin-film solar cells based on various materials such as amorphous silicon, Cadmium Telluride/Cadmium Sulfide (CdTe/CdS), and Copper Indium Gallium Selenide/Copper Zinc Tin Sulfide (CIGS/CZTS) were discovered. With these types of thin-film cells as well, the use of solar cells is more flexible for various applications mainly due to their lighter weight. Although the efficiency of their photovoltaic effect or light-to-electricity conversion is generally lower than that of crystalline silicon solar cells, these thin-film solar cells are efficient in absorbing light in dimmer conditions.